การกำจัดตะกั่วออกจากน้ำเสียโดยใช้เปลือกหอยแครงและเปลีอกหอยแมลงภู่ - จรรยาพร พุ่มงาม (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
Cockle shells and mussel shells, residual materials available locally, were used to study the removal of lead from waste water. The non-continuous or a batch test was used to evaluate the adsorption efficiency under various factors. Freundlich adsorption isotherm was used in this system. The continuous study using column was applied in order to evaluate the performance of shells. The specific surface area, pore size and amount of calcium carbonate in cockle shells were higher than mussel shells. Study of efficiency of the shells using various size of shells dried at different temperature showed that cockle shells of 20-60 meshsize dried under sunshine in summer had the best of lead removal. The adsorption constant from Freundlich adsorption isotherm was found to be 9.46x10[superscript 5] milligrams lead per gram cockle shell. The optimum pH for the lead adsorption was between 6.3-8.8 and the adsorption decreased with pH. The removal occurred mainly through the dissolution of CaCO[subscript 3] followed by the precipitation of cerrussite (lead carbonate) near the surface of the shells. Micro precipitates formed were then adsorbed to the surface of shell particles. The continuous adsorption column test has been performed for breakthrough curve construction using lead-contaminated water collected from a battery factory. The lead concentration of the water was 5.98 mg/L. The column with a diameter of 1.9 cm packed with cockle shells of 2.3 cm high could treat the lead contaminated water up to 6 litres before the lead concentration in the effluent was above 0.2 mg/L which was the standard for waste water set by the Ministry of Industry. Adsorption capacity was 8.6 milligram lead per gram cockle shell